A Replicable Model of Recruitment for Longitudinal Research of Preterm Infants. Issue 5 (September 2019) - Gordon, Jessica M.; Proschold, Kaitlyn; Harville, Cedric; Dutra, Samia; Groer, Maureen
Abstract : Background: Recruitment and retention in longitudinal studies can be challenging because the numbers of participants may not adequately reflect the targeted population. Objectives: The aim of the study was to present a replicable pathway model of recruitment via retrospective chart review and describe outcomes of the recruitment methods used in the model on enrollment, scheduling, and attrition. Methods: This retrospective chart review included recruitment data from participants of a parent grant ( n = 99) that met chart review inclusion criteria ( n = 47) for a follow-up study measuring microbiome data of preterm infants at toddler and preschool age. Results: Over a 3-year recruitment period, 25 of the 47 participants eligible for recruitment were enrolled in the follow-up study. Initial contact was more likely to be performed via mail and e-mail for first time points and via phone for subsequent contact and second time points. For scheduling, phone contact was the method utilized most frequently for both groups, with online scheduling second when introduced in the preschool group. Two participants were lost to follow-up, resulting in an attrition rate of 8%. Discussion: This recruitment pathway model offers researchers multiple recruitment methods for initial contact and scheduling that may be useful in contacting more participants to positively affect enrollment and reduce attrition rates for longitudinal cohorts. The innovation of recruitment methods via Facebook for initial contact and online scheduling are new methods with promise and multiple benefits for the research staff and participants.